1996
DOI: 10.1115/1.2787217
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Equations Governing a Material With Prescribed Temperature-Dependent Density With Application to Nonisothermal Plane Poiseuille Flow

Abstract: The standard practice in the literature for modeling materials processing in which changes in temperature induce significant volume changes is based on the a posteriori substitution of a temperature-dependent expression for density into the governing equations for an incompressible material. In this paper we show this ad hoc approach misses important terms in the equations, and by example show the ad hoc equations fail to capture important physical effects. First we derive the three-dimensional equations which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…A general proof can be found in (Rooney et al 1999) for thermomechanical processes satisfying the Gibbs conditions (Gibbs 1873(Gibbs , 1878. The local illposedness of the constrained theory (Cao et al 1996) found in this study certainly contradicts both the unconstrained theory and the common experience with nonisothermal viscous uids. Consequently, its direct use in transient ow phenomenon is not advised.…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…A general proof can be found in (Rooney et al 1999) for thermomechanical processes satisfying the Gibbs conditions (Gibbs 1873(Gibbs , 1878. The local illposedness of the constrained theory (Cao et al 1996) found in this study certainly contradicts both the unconstrained theory and the common experience with nonisothermal viscous uids. Consequently, its direct use in transient ow phenomenon is not advised.…”
contrasting
confidence: 77%
“…1 Introduction Cao et al (1996) developed a thermomechanically consistent constrained theory for materials with prescribed temperature-dependent density. This theory successfully captures the expansion cooling phenomenon observed in nonisothermal steady state Poiseuille ows of viscous uids (Winter 1977, Cao et al 1996 while the ad hoc theories (Kase and Matsuo 1965, Sabhapathy and Cheng 1986, Hayashi et al 1992, where a temperature-dependent density is a posteriori inserted into the classical theory for incompressible materials (Bird et al 1987), fail. In this regard, the constrained theory of Cao et al's marks a notable theoretical advance in modeling steady state nonisothermal ows.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This modeling advance, combined with the experimental advances described above, pushes our resolution of dynamic surface tension to fractions of a millisecond. An important result in [2] is the following: The rate and form of the decay can be inferred from downstream measurements, avoiding the need for measurements near the nozzle where rapid surface tension decay takes place. In [12] the equations for oscillating jets are extended to allow for shear-rate dependent viscosity.…”
Section: Modeling and The Inverse Problemmentioning
confidence: 99%
“…Thermally induced shrinkage is an important feature of this process, and the state-of-the art modeling of the effect was a posteriori insertion of a temperature-dependent density function into the equations governing an incompressible fluid. In [2] we showed that this approach is thermodynamically inconsistent (it violates the second law), and derived, through the theory of a thermomechanically constrained material, a model which does not violate the second law. When applying this thermomechanically consistent model to pipe flows in that paper and [1], we predicted features qualitatively different than the commonly employed ad hoc model, in agreement with predictions based on the fully compressible theory.…”
Section: Thermomechanics and Stability Of Materials With Temperature-mentioning
confidence: 99%